Peran Emosi Positif Dalam Memediasi Store Atmosphere dan Store Image Terhadap Pembelian Impulsif - Ernawati, Ernawati; Efendi, Bahtiar (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2024)
In business competition, retailers are expected to increase their sales so they can compete with other retailers. The phenomenon of impulsive buying behavior is a challenge for retailers where they are required to be able to create emotional interest such as provoking consumers' passion to buy and consume a particular product. The aim of the research is to prove how positive emotions mediate store atmosphere and store image and influence impulse buying. This research uses a quantitative approach, namely an approach that emphasizes analysis of numerical data processed using statistical methods. Quantitative research is a type of research that produces discoveries that can be achieved (obtained) using statistical procedures or other means of quantification (measurement). Then it is measured using SmartPLS (Partial Least Square) software starting from hypothesis testing. The results of this research are that store atmosphere has a positive effect on impulse buying, store image has a positive effect on impulse buying, store atmosphere has a positive effect on positive emotions, store image has a positive effect on positive emotions, positive emotions have a positive effect on impulse buying, positive emotions mediate the positive effect of store atmosphere. on impulse buying, positive emotions mediate store image having a positive effect on impulsive buying